2007
DOI: 10.1093/nar/gkl1150
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of RNA cap guanine-N2 methyltransferases from Giardia lamblia and Schizosaccharomyces pombe

Abstract: RNA cap guanine-N2 methyltransferases such as Schizosaccharomyces pombe Tgs1 and Giardia lamblia Tgs2 catalyze methylation of the exocyclic N2 amine of 7-methylguanosine. Here we performed a mutational analysis of Giardia Tgs2, entailing an alanine scan of 17 residues within the minimal active domain. Alanine substitutions at Phe18, Thr40, Asp76, Asn103 and Asp140 reduced methyltransferase specific activity to <3% of wild-type Tgs2, thereby defining these residues as essential. Alanines at Pro142, Tyr148 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 41 publications
4
50
0
Order By: Relevance
“…The enzyme Tgs1 is responsible for TMG capping (Mouaikel et al 2002;Komonyi et al 2005;Lemm et al 2006;Hausmann et al 2007). Purified yeast and human Tgs1 catalyze two successive methyltransfer reactions from AdoMet to the N2 atom of guanosine nucleotides via a distributive mechanism (Hausmann and Shuman 2005a;Hausmann et al 2008;Benarroch et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme Tgs1 is responsible for TMG capping (Mouaikel et al 2002;Komonyi et al 2005;Lemm et al 2006;Hausmann et al 2007). Purified yeast and human Tgs1 catalyze two successive methyltransfer reactions from AdoMet to the N2 atom of guanosine nucleotides via a distributive mechanism (Hausmann and Shuman 2005a;Hausmann et al 2008;Benarroch et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mutational studies of several Tgs enzymes identified a suite of essential amino acid side chains that were predicted to form the binding pockets for the AdoMet donor and m 7 G acceptor (Mouaikel et al 2003;Hausmann and Shuman 2005b;Hausmann et al 2007Hausmann et al , 2008Simoes-Barbosa et al 2008;Benarroch et al 2009). Most of the substrate interactions inferred from mutational studies and modeling exercises were confirmed by the crystal structure of human Tgs1 (hTgs1) in a ternary complex with m to the triphosphate moiety of m 7 GTP ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, TGS1 hypermethylates the m7G RNA cap to a trimethylguanosine (TMG; m 2,2,7 guanosine) cap (28,(33)(34)(35)(36)(37). A nuclear isoform of human PIMT has been shown to have methyl transferase activity (30)(31)(32).…”
mentioning
confidence: 99%
“…TGS1 hypermethylates the m7G RNA cap to a trimethylguanosine (TMG; m2,2,7 guanosine) cap. [28][29][30][31][32][33] A nuclear isoform of human PIMT has been shown to have methyl transferase activity. 28,34,35 In the new finding, PIMT was found to hypermethylate selectively the RNA-cap of unspliced and partially spliced HIV-1 transcripts and to increase their cytoplasmic distribution 23 ( Fig.…”
Section: What Does Pimt Do For Hiv-1 Rna?mentioning
confidence: 99%